High-performance carrageenan film based on carrageenan intercalated layered double hydroxide with enhanced properties: Fire safety, thermal stability and barrier effect. (September 2018) - Li, Zhi; Wang, Jiang; Expósito, Daniel Fernández; Zhang, Jing; Fu, Can; Shi, Dean; Wang, De-Yi
Abstract: Bio-based polysaccharides show potentials to substitute petroleum-based polymers. Herein, κ-carrageenan intercalated layered double hydroxide (LDH-Carra) was prepared to impart κ-carrageenan film with improved thermal stability, fire safety and gas barrier. Results showed that the temperature at 5% mass loss of carrageenan film with 3 wt% LDH-Carra (Carra/LDH-Carra) was increased by 55 °C. Carra/LDH-Carra presented 42.9% and 52.0% reduction of peak heat release rate and total heat release respectively with higher LOI and self-extinguishment in horizontal burning test. In parallel, LDH-Carra endowed Carra film with 18% and 200% increment of tensile strength and tensile modulus. Barrier test revealed approximately 50% reduction of oxygen permeability without deterioration of transparency after addition of LDH-Carra. The property enhancement was relevant to the exfoliated dispersion of LDH nanosheets in Carra film. Prospectively, polysaccharides intercalated LDH serves a feasible approach to multifunctional enhancement of polymers. Highlights: κ-carrageenan intercalated LDH (LDH-Carra) was prepared via co-precipitation. Carra film with LDH-Carra showed enhanced thermal stability and fire safety. Carra film with LDH-Carra presented improved gas barrier and mechanical property.